1968
DOI: 10.1128/jb.96.4.987-996.1968
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determination of Resistance to Acriflavine, Phenethyl Alcohol, and Sodium Dodecyl Sulfate in Escherichia coli

Abstract: Wild-type strains of Escherichia coli K-12 are resistant to acriflavine. Gene acrA + which determines resistance to acriflavine is located near the lac region of the chromosome. This gene determines not only resistance to basic dyes but also resistance to phenethyl alcohol. Acriflavine resistance was transmitted, together with phenethyl alcohol resistance, from a resistant Hfr strain to a sensitive recipient by mating. Reversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0

Year Published

1972
1972
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 25 publications
3
32
0
Order By: Relevance
“…Mutations in the acrA locus are known to render Escherichia coli hypersusceptible to basic dyes, detergents and antibiotics (Nakamura, 1965;1968), The observation that Received 23 September t994;revised 30 November 1994;accepted 13 December, 1994. ^'For correspondence, Tel.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the acrA locus are known to render Escherichia coli hypersusceptible to basic dyes, detergents and antibiotics (Nakamura, 1965;1968), The observation that Received 23 September t994;revised 30 November 1994;accepted 13 December, 1994. ^'For correspondence, Tel.…”
Section: Introductionmentioning
confidence: 99%
“…In the past several years, similar mutants have been isolated by other workers. [2][3][4][5][6][7][8] By their spectrum of sensitivity to antibiotics and to other agents, and other properties which we will discuss later, it is obvious that most of these independently isolated mutants are probably the result of a similar defect.…”
mentioning
confidence: 99%
“…Previously, one (H.N.) of us found that the cellular response to acriflavine (AF), a derivative of acridine, of E. coli K-12 was determined by a gene acrA located near the lac gene (17,18). The acrA mutants accumulate more and thus are more sensitive to acriflavine and other basic dyes than acrA+ strains (15,16).…”
mentioning
confidence: 99%
“…The acrA mutants accumulate more and thus are more sensitive to acriflavine and other basic dyes than acrA+ strains (15,16). The AF-sensitive mutants are also sensitive to lipophilic substances such as phenethyl alcohol and sodium dodecyl sulfate (18,19).…”
mentioning
confidence: 99%